STEM in Science Learning in the Era of The Industrial Revolution 4.0 - Melinda, Sri; Sa'ud, Udin Syaefudin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The Industrial Revolution 4.0 related to technology and information brought changes to human lifestyles. This change immediately demands the world of education, especially students, to have more massive competencies. Some of these competencies include science, technology, critical thinking, creativity, and innovation, working together, communicating well, and having self-confidence. Not only students but also teachers are required to be creative and innovative, especially in teaching students in the school environment. The approach that can be used in teaching students according to the demands of the 4.0 era is the Science, Technology, Engineering, and Mathematics (STEM) approach. The purpose of this study is to explain more broadly about STEM to science learning in the 4.0 era. This study uses a literature review study of relevant research results in the form of journals and articles related to STEM in science learning. This literature review will contribute as a reference and increase the insight of researchers and readers. In addition, this study is expected to open up new ideas for deeper research on STEM.